The trust–NPS correlation: The role of trust in promoting customer loyalty in Swiss financial institutions - Vanessa Gabriela Yarza Navarro-Schär; Eric Eller; Marco Schulz; Eva Lermer (PLoS ONE, 2025)
The Net Promoter Score (NPS) is a widely used key performance indicator (KPI) for measuring customer loyalty and guiding customer-centric strategies. While customer trust has been identified as an important influencing factor for NPS, existing research treats trust as a unidimensional construct, leaving the specific trust components that drive customer loyalty behaviors largely unexplored. This study addresses this theoretical gap by examining the relationship between various trust components and NPS in the financial services sector. A survey of 1,370 Swiss consumers assessed trust across ten theoretically-derived dimensions alongside their NPS ratings for five financial service companies. Employing median-split analysis, results demonstrate that high customer trust is associated with a significantly higher NPS (+36.5) compared to low trust (−68.6). Critically, quantile regression analysis revealed heterogeneous effects of trust components across different NPS distribution levels, with ability, experience, and reputation showing consistent positive effects across all quantiles. In contrast, joint interests and continuity emerged as relevant only at higher NPS quantiles, while reciprocity proved significant exclusively at the 25th percentile, demonstrating that distinct trust determinants become salient depending on customers’ advocacy levels. These findings challenge prevailing theoretical assumptions about customer trust’s homogeneous influence on customer loyalty, revealing instead a differentiated pattern of trust component effects. The study advances trust theory by demonstrating that trust dimensions not only vary in their influence on customer advocacy behaviors but also exhibit different effect patterns across the NPS distribution, contradicting assumptions of uniform trust impact on loyalty outcomes. The results indicate that NPS optimization requires strategic focus on specific trust dimensions, particularly those demonstrating consistent positive associations across quantile levels. This research contributes novel theoretical insights into the conditional trust-loyalty relationship while providing empirically-grounded guidance for customer-centric business strategies.